Melioidosis: a clinical overview - Limmathurotsakul, D; Peacock, S (2011)
Introduction: melioidosis, an infection caused by the environmental Gram-negative bacillus Burkholderia pseudomallei, has emerged as an important cause of morbidity and mortality in Southeast Asia and northern Australia. Sources of data: a review of the literature using PubMed. Areas of agreement: approaches to diagnosis and antimicrobial therapy. Areas of controversy: whether seroconversion signals the presence of a quiescent bacterial focus and an increase in long-term risk of melioidosis. Areas timely for developing research: melioidosis is potentially preventable, but there is a striking lack of evidence on which to base an effective prevention programme. An accurate map defining the global distribution of B. pseudomallei is needed, together with studies on the relative importance of different routes of infection. There is a marked difference in mortality from melioidosis in high-income versus lower income countries, and affordable strategies that reduce death from severe sepsis (from any cause) in resource-restricted settings are needed. © The Author 2010. Published by Oxford University Press. All rights reserved.